Implementation of Discovery-Inquiry Methods with Work Sheet Illustrated Media to Improve Student’s Critical Thinking Skills of Science Lessons in Indonesia’s Border Elementary School - Tri Novita Indriyati (International Journal of Chemistry Education Research, 2019)
This study aims to improve students' critical thinking skills (CTS) in disadvantaged, outermost and foremost areas, namely in Indonesia's border elementary schools which are full of limited educational facilities. This research was conducted on science subjects in grade VI SDN 29 IDAI on the balance of ecosystems. The method used for the research is the experimental method, which is Quasi Experiment because conditions do not allow for the control class to be held. The research design is one group pretest posttest design, where before the treatment is given, the sample is first given a pretest (initial test) and at the end of the learning sample is given a posttest (final test). CTS aspects developed in this study include identifying criteria for possible answers, mentioning examples, giving reasons, and drawing conclusions. Based on the results of data analysis in the form of the results of the pre-test and post-test, there was an increase in students' average critical thinking skills, starting from 32% (less) in the pre-test to 75% (good) in the post-test. The application of discovery-inquiry method with work sheet illustrated media is also able to increase student learning outcomes to an average value of 72.38 with a graduation rate. The minimum criteria for completeness in classical is 84.62%.